A Biomechanical Approach to Investigate the Applicability of the Lake-Thomas Theory in Porcine Aorta - Yamamoto, Kenzo; Hara, Kazuaki; Mizuno, Hayato Laurence; Ishikawa, Kosuke; Kobayashi, Etsuko; Akagi, Yuki; Sakuma, Ichiro (International Journal of Integrated Engineering, 2021)
Robot-assisted surgeries are procedures where a physician performs surgical maneuvers by operating a robot. One of the main limitations is the difficulty in transferring the surgeonâ€™s multiple skills onto the robotic system. Such skills include the ability to estimate the maximum applicable force before damaging the tissue. To implement this skill onto a robotic system, a mathematical model for tissue damage must be developed. The objective of this study is to measure the fracture characteristic in porcine aorta, to then investigate whether an existing fracture model can be applied onto biological tissues. Due to the similarity in the mechanical response between biological tissues and polymeric materials, the model chosen for this study was the Lake-Thomas model. This is the first paper with the aim of validating this model with biological tissues. Two main findings are reported in this investigation. We found that porcine thoracic aorta tears in a specific way which is directly correlated to the tensile direction. The second finding is that an anisotropic linear relationship exists between the critical tearing energy and the elastic modulus, and the elastic modulus to the -0.5th power. These results are discussed based on the elastin and collagen fibers, as well as established mathematical equations describing polymer mechanics